Development of Reading Comprehension Teaching Materials Using the CIRC Model in Primary School - Jumaini Jumaini (International Journal of Educational Dynamics, 2019)
motivated by teaching materials that are used by teachers which do not contain the complete reading process (pre-reading, reading, and post-reading). This study aims to develop reading comprehension teaching materials using the CIRC model for elementary school class V that is valid, practical, and effective. This type of research is development research. This study uses the ADDIE model which consists of 5 stages, namely: the stage of analysis, design, development, and implementation, and evaluation. Validity test data is obtained through assessment sheets of teacher and student responses. Effectiveness is seen from the activities of students, assessment of the process and results of the test of reading comprehension of students. Based on the results of the validity, practicality, and effectiveness tests obtained teaching materials that are valid, practical, and effective, and able to improve reading comprehension skills. It can be concluded that teaching reading comprehension materials using the CIRC model developed can be used in reading comprehension learning in grade V of Elementary School.